Physiology, asthma and injuries in high-performance adolescent and young adult cross-country skiers - Oliván-Gracia, S.; Oliván-Gonzalvo, G. (International Journal of Advanced Multidisciplinary Research and Studies, 2023)
Cross-country skiing is a winter sport that consists of traveling generally long distances on uneven terrain with slopes that may be steep, but not continuous. A narrative review of the physiology, asthma, and injuries in high performance adolescent and young adult cross-country skiers is carried out. From the point of view of physiology, this sport has helped to acquire new knowledge about the limits of human performance and regulatory capacity. The main physiological effects on the respiratory, cardiovascular, musculoskeletal, and energy systems are described. Being a high-performance cross-country skier is an independent risk factor associated with developing asthma, with the prevalence being 2 to 2.5 times higher and the age of onset later compared to non-skiers. It is usually well-controlled and requires regular maintenance treatment. This disorder is not an obstacle to practicing this sport. While it is generally a low-impact and low-risk sport, injuries can still occur. The most common acute traumatic and overuse injuries are described. Most injuries can be prevented and treated conservatively. Cross-country skiing is a safe and physiologically ideal form of physical exercise, both recreationally and competitively.